Kefahaman dan Keperluan Pendidikan Perkahwinan di Malaysia - Siti Nubailah Mohd Yusof; Zuria Mahmud; Salleh Amat (Universiti Sains Islam Malaysia, 2024)
Marriage education is a form of dissemination of information designed to help individual and couples to achieve happiness and success in marriage. Nevertheless, marriage education is not just a pre-marital course, but it is a knowledge and skills needed to have either at the beginning of marriage and it continued along marriage lasted. Therefore, this study aimed to investigate the views of experts and public about marriage education in Malaysia. The study collected data through structured interviews with 12 samples, 3 public and 9 experts consisting lecturers, registered counselors and religious officers. Data were managed in NVivo 8 using thematic analysis approach. Outcomes from the interview obtained two main themes 1) understanding of marriage education and 2) necessity of marriage education.